2019
DOI: 10.33633/es.v1i2.2175
|View full text |Cite
|
Sign up to set email alerts
|

EFL Learners’ Listening Strategy Awareness viewed from Their Learning Styles in the Extensive Listening Class

Abstract: Albeit listening comprehension as the vital role of language input, most EFL students have a somewhat negligent concern of it in the process of mastering EFL. Accordingly, the listening educators need to confirm students' listening strategy awareness related to their learning styles for enhancing the quality of teaching listening. To this end, the study aims at assaying EFL students' listening strategy awareness between visual, auditory, and kinesthetic learners who got an explicit strategy instruction of Exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Offering the students an opportunity to freely select an online audio recording based on their interests for summarization and reflection supported their autonomous online language learning. These positive points were also in line with the results reached by Onoda (2012), Milliner (2017, Saputra and Fatimah (2018), Astuti and Dj (2019), Strong et al (2023), andMulyadi et al (2023). These studies indicated that practicing extensive listening through the authentic materials offered by such online platforms led to improving students' listening skills and self-confidence, in addition to enriching their English vocabulary and enhancing their autonomy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Offering the students an opportunity to freely select an online audio recording based on their interests for summarization and reflection supported their autonomous online language learning. These positive points were also in line with the results reached by Onoda (2012), Milliner (2017, Saputra and Fatimah (2018), Astuti and Dj (2019), Strong et al (2023), andMulyadi et al (2023). These studies indicated that practicing extensive listening through the authentic materials offered by such online platforms led to improving students' listening skills and self-confidence, in addition to enriching their English vocabulary and enhancing their autonomy.…”
Section: Discussionsupporting
confidence: 81%
“…ELLLO gives students various authentic listening materials that enable them to practice using English as a Lingua Franca (Milliner & Chaikul, 2020). Students' experiences with ELLLO were evaluated by Mulyadi et al (2023). Using an open-ended questionnaire administered to 96 participants, it was revealed that ELLLO is an effective alternate learning medium to develop students' practice of listening skills in and out of the classroom.…”
Section: Extensive Online Listeningmentioning
confidence: 99%